When Source is Also Receiver. Issue 4 (December 2013) - Halmrast, Tor
Musicians (and low budget acousticians) often judge the acoustics of a venue by clapping, shouting or making other kinds of more or less impulse-like sounds. In such situations, the source and the receiver are (almost) at the same position. This is a different situation than for standard measurements of room acoustics, where there is a (long) distance between the sound source (loudspeakers, pistols, balloons and musical instruments) and the receiver (microphone, ear). The sonic experience must be totally different, but still we trust our clapping and our ears. We probably "recalculate" so that reverberation times etc. judged in such a way "by ear", are often quite correct. How can this be? And: Can we learn from how a blind person uses click sounds made with the mouth in order to "see"/echolocate surfaces and objects by the ears? In both situations the position of the source and the receiver are (almost) the same. In this paper we compare the results from room acoustic measurements taken from "in-ear"-recordings of own hand claps with more standardised measurements in three types of rooms: A big, reverberant foyer, a concert hall and a small living room/music room.